2015
DOI: 10.3389/fmicb.2015.00134
|View full text |Cite
|
Sign up to set email alerts
|

The nasal microbiota in health and disease: variation within and between subjects

Abstract: Chronic rhinosinusitis (CRS) affects approximately 5% of the adult population in Western societies and severely reduces the patient’s quality of life. The role of bacteria in the pathogenesis of this condition has not yet been established with certainty. However, recent reports of bacterial and fungal biofilms in CRS highlight a potential role for these microorganisms. In this study, 16S rRNA gene-targeted amplicon pyrosequencing and qPCR were used to determine the composition and abundance, respectively, of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
164
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(194 citation statements)
references
References 81 publications
29
164
1
Order By: Relevance
“…Molecular techniques identify significantly more organisms than standard cultures [15], shedding light on complex bacterial communities within healthy sinuses that had previously been assumed to be sterile. The normal microbiota of the sinuses is currently not well defined and appears to vary widely among individuals [2, 68]. Evidence suggests that diminished bacterial diversity and richness are associated with CRS [2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques identify significantly more organisms than standard cultures [15], shedding light on complex bacterial communities within healthy sinuses that had previously been assumed to be sterile. The normal microbiota of the sinuses is currently not well defined and appears to vary widely among individuals [2, 68]. Evidence suggests that diminished bacterial diversity and richness are associated with CRS [2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…442 Yan et al 441 demonstrated differences between microbiota of the anterior nares vs the deeper anatomic subsites, but a thorough comparison within the sinuses has yet to be published. In contrast to the rich assemblages of bacteria that populate the sinuses in the healthy state, CRS patients are colonized by a similar quantity of bacteria overall, but display qualitatively different microbial communities than their healthy counterparts.…”
Section: S55mentioning
confidence: 99%
“…Swab samples were thawed on ice and placed into a sterile Lysing Matrix E tube (MP Biomedicals, Australia). Genomic DNA was extracted from the paired swabs using the AllPrep DNA/RNA isolation kit (Qiagen), as described previously (36). A negative extraction control to test for contamination originating from the DNA isolation kit was carried out in triplicate using 200 l of sterile water.…”
Section: Patient Informationmentioning
confidence: 99%